Facile fabrication of hyaluronated starch nanogels for efficient docetaxel delivery. (July 2019) - Yu, Hyeong Sup; Koo, Mijin; Choi, Sung-Wook; Na, Kun; Oh, Kyung Taek; Youn, Yu Seok; Lee, Eun Seong
In this study, we designed and synthesized polysaccharidic nanogels comprising starch cross-linked with hyaluronic acid. These hyaluronated starch nanogels were prepared by cross-linking primary hydroxyl groups in polysaccharides (starch and hyaluronic acid) and epoxide groups in 1, 4-butanediol diglycidyl ether (used as a cross-linking agent). The nanogels take advantage of hyaluronic acid as a specific ligand for CD44 receptors overexpressed on tumors and the hyaluronic acid/starch core as a compartment for the encapsulation of docetaxel (as model antitumor drug). Here, hyaluronic acid can be enzymatically degraded by tumor cell–specific enzyme (e.g. hyaluronidase-1), which could significantly accelerate docetaxel release from the nanogels. Our experimental results demonstrate that the nanogels promote the release of docetaxel content in the presence of hyaluronidase-1 enzyme. As a result, the nanogels selectively inhibited MCF-7 (with CD44 receptor and hyaluronidase-1 enzyme) tumor cell growth in vitro, suggesting their therapeutic potential for efficient tumor ablation.